1996
DOI: 10.1063/1.361405
|View full text |Cite
|
Sign up to set email alerts
|

Grain boundary diffusion effects on the sputter depth profiles of Co–Ag bilayers

Abstract: We investigated the effects of surface roughness and grain boundary diffusion (GBD) at elevated temperatures on the Auger-electron-spectroscopy sputter depth profiles of Co–Ag bilayers and the GBD process of Ag atoms in Co. The Ag layer in the Ag/Co bilayer is transformed from a uniform layer to discrete islands by heat treatment. Enhanced mobility during sputtering at elevated temperatures makes Ag atoms migrate continually from islands to cover neighboring exposed Co, which reduces the size of Ag islands. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Figure 5 shows the TiN layer thickness dependence on atomic fraction σ at elevated temperatures. When we assume that the accumulated Cu atoms are uniformly distributed in the surface region, that the probability of a Cu atom finding a vacant surface site is proportional to the fraction of the surface which is not yet covered with Cu, the top-layer thickness dependence of the accumulation surface concentration can be described as [14,17] σ = 1 − exp − P l (4) Fig. 5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 5 shows the TiN layer thickness dependence on atomic fraction σ at elevated temperatures. When we assume that the accumulated Cu atoms are uniformly distributed in the surface region, that the probability of a Cu atom finding a vacant surface site is proportional to the fraction of the surface which is not yet covered with Cu, the top-layer thickness dependence of the accumulation surface concentration can be described as [14,17] σ = 1 − exp − P l (4) Fig. 5.…”
Section: Resultsmentioning
confidence: 99%
“…To study this grain boundary diffusion (GBD) in thin films at low temperatures, the surface accumulation [15][16][17] and depth profiling [18,19] have been the most commonly used methods in highly sensitive surface analytical techniques, such as Auger electron spectroscopy (AES), secondary ion mass spectroscopy (SIMS), and X-ray photoelectron spectroscopy (XPS). The surface accumulation method has many advantages over the depth profiling method; it is more sensitive to the details of the source, and the surface sink conditions at the grain boundaries are required to produce a measurable concentration on the accumulation surface.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al [11] investigated the grain boundary diffusion (GBD) process of Co/Ag bilayer on oxidized Si wafer. They found that the Ag atoms diffuse along the grain boundaries through the Co layer to the surface, and then spread out along the surface to accumulate 2-3 ML Ag on Co layer in a layer-by-layer growth mode.…”
Section: Resultsmentioning
confidence: 99%
“…According to our knowledge, in the literature only one article reports this phenomenon [13]. The grain boundary diffusion is described in several immiscible systems [14][15][16].…”
Section: Introductionmentioning
confidence: 99%